2023
DOI: 10.7717/peerj.15257
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization of the xyloglucan endotransglucosylase/hydrolase gene family in Solanum lycopersicum L. and gene expression analysis in response to arbuscular mycorrhizal symbiosis

Abstract: Xyloglucan endotransglucosylase/hydrolases (XTHs) are a glycoside hydrolase protein family involved in the biosynthesis of xyloglucans, with essential roles in the regulation of plant cell wall extensibility. By taking advantage of the whole genome sequence in Solanum lycopersicum, 37 SlXTHs were identified in the present work. SlXTHs were classified into four subfamilies (ancestral, I/II, III-A, III-B) when aligned to XTHs of other plant species. Gene structure and conserved motifs showed similar compositions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 81 publications
1
4
0
Order By: Relevance
“…Further, phylogenetic analysis indicated that MaXTH protein families were clustered into five groups ( Figure 1 ), similar to those observed for XTH proteins from sweet cherry [ 26 ]. Interestingly, the MaXTH proteins belonging to the same group demonstrated similar gene structures ( Figure 1 ) and conserved sequence expression, which is consistent with previously documented literature [ 11 , 20 ], suggesting that XTH members within the same group may exhibit analogous functionalities. Moreover, most of the MaXTH genes demonstrate the presence of two main conserved domains (Glyco_hydro_16 and XET_C domain) ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Further, phylogenetic analysis indicated that MaXTH protein families were clustered into five groups ( Figure 1 ), similar to those observed for XTH proteins from sweet cherry [ 26 ]. Interestingly, the MaXTH proteins belonging to the same group demonstrated similar gene structures ( Figure 1 ) and conserved sequence expression, which is consistent with previously documented literature [ 11 , 20 ], suggesting that XTH members within the same group may exhibit analogous functionalities. Moreover, most of the MaXTH genes demonstrate the presence of two main conserved domains (Glyco_hydro_16 and XET_C domain) ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 90%
“…Based on the M. alba genome, 22 XTH genes were identified based on our strictest identification workflow and labeled as MaXTH-1 to MaXTH-22 . The number of identified XTH genes was notably less compared to various other species, including tobacco (56), wheat (71), Solanum lycopersicum (37), and Glycine max (61) [ 11 , 18 , 22 , 52 ]. It is widely acknowledged that the functional attributes of genes are intricately linked to their structural and physicochemical characteristics [ 20 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant hormones play an important role in regulating lignin biosynthesis, organic matter accumulation, and other physiological activities and eventually influence the growth and development of plant tissues and organs [ 16 , 17 , 18 ]. Auxins (IAA) are frequently associated with stem elongation and root development and can promote or inhibit apical dominance [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%